If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + 2) = 12 Reorder the terms: 2(2 + y) = 12 (2 * 2 + y * 2) = 12 (4 + 2y) = 12 Solving 4 + 2y = 12 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2y = 12 + -4 Combine like terms: 4 + -4 = 0 0 + 2y = 12 + -4 2y = 12 + -4 Combine like terms: 12 + -4 = 8 2y = 8 Divide each side by '2'. y = 4 Simplifying y = 4
| 0=2x^2-16x+38 | | 36=.5(x*2x) | | 44=2(3w+w) | | x^3-5x^2+3x-5x-6= | | 9+x=93 | | 2.4=x+3.7 | | 4(d+6)= | | 890/2 | | -3x^3+10x^2-3x=0 | | 5(2c+3)-8=3(4c+2)-2c | | 0.5x-0.3(50+x)=0.3(50) | | 6+7x=4x+1 | | 27=x3/2 | | 5(4-6x)=8+6(7+2x) | | 4^2/2=3y | | 2(7b-4)=b-21 | | 5x+8+7x+10=90 | | 3(3+2x)=-45 | | 24k^2-31k-36=-k | | n(5n+4)=0 | | h=t*t+14t+0 | | x^2(8x-3)4(8x+3)=0 | | h(x)=x^4+2x^3-3x^4 | | 2x-17+3x+7=180 | | -2/3-4/3 | | (12-v)=-3 | | 4X+2Y=336 | | (2x-1)+(6x+2)+(5x+3)=180 | | -2/3-4/3=0 | | 3a+-b=6 | | 4x-2(-1)=4x-23(-5) | | y=3x+8-(12x) |